Depopulation and its Socio-Economic Consequences. Romania Case Study - Radu Săgeată; Dragoș Baroiu; Cristina Dumitrică (Transylvanian Review of Administrative Sciences, 2024)
Depopulation is a characteristic phenomenon for the Central and Eastern European space that gained in amplitude especially after 1990 in the context of political-ideological changes that affected the states of this region and that also led to changes in demographic behavior. These consisted, on the one hand, in the abolition of pro-natalist policies from the communist period and, on the other hand, in the intensification of emigration flows in connection with the economic and social discrepancies and the free movement of persons. In this context, the paper analyzes the evolution of Romania’s population in a global and European context, the factors that determined its sharp population decline, as well as its economic and social consequences. Also, the demographic characteristics of Romania and future trends regarding the peculiarities and dynamics of the Romanian population are highlighted.